Smoking Behaviors and Perceived Health Risks Among Out-of-School Youth in Tella, Taraba State - Isaac John Umaru; Solomon O. Asare; Tyem Lawal Danjuma; Inemesit Samuel Essien; Ingwu Joseph Akem; Genevieve A. Yeboah; Julius Ishaya Salman; Kwabena Owusu Amoah; Precious Chioma Jack; Hauwa A. Umaru; Maayam Usman Ahmed (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2026)
Tobacco use among adolescents remains a significant public health concern, particularly among out-of-school youth who often have limited access to formal health education and support systems. In response to anecdotal indications of increasing smoking behavior in Tella, this study aimed to assess the prevalence, patterns, and determinants of smoking among out-of-school youth, examine their perceptions of smoking-related health risks, and identify the socio-cultural and economic factors associated with tobacco use. A cross-sectional descriptive survey was conducted using structured questionnaires administered to a purposive sample of out-of-school youth aged 13–24 years, and the data were analyzed using descriptive statistics and presented in tabular form. The findings showed that 58% of respondents were current tobacco users, with cigarettes as the most commonly used product (60%), while 40% reported initiating smoking before the age of 15. Although 70% acknowledged that smoking is harmful, only 35% could identify specific smoking-related diseases, and 45% believed that occasional smoking was not harmful. Peer pressure (60%) and stress related to unemployment (50%) emerged as the most frequently cited reasons for smoking. The respondent profile further indicated that most participants were male (65%), aged 17–21 years (58%), and characterized by high levels of unemployment (42%) and informal labor participation (30%). The study concludes that out-of-school youth in Tella are highly vulnerable to tobacco use due to the combined effects of limited education, economic hardship, peer influence, and cultural norms. These findings highlight the need for integrated interventions that combine health education, peer-based support, economic empowerment, and policy enforcement to reduce tobacco use and promote healthier lifestyles among this at-risk population.